A study of wake effects on the drag of Ahmed׳s squareback model at the industrial scale. Issue 145 (October 2015) - Grandemange, M.; Cadot, O.; Courbois, A.; Herbert, V.; Ricot, D.; Ruiz, T.; Vigneron, R.
Abstract: Experiments are performed at industrial scales over the Ahmed geometry, i.e. at a Reynolds number of Re = 2.5 × 10 6 based on the height of the body. The shape of the squareback geometry is first optimized to make an initial substantial drag reduction. The separated flow at the trailing edge is orientated by introducing chamfers at the top and bottom edges. A parametric study based on both chamfered angles leads to an optimized Ahmed geometry having a drag of 5.8% lower than the reference squareback model. It is evidenced that this optimized geometry produces 4 intense longitudinal vortices that still contribute significantly to the drag. The effect of a sideslip yaw angle is studied. As expected, it is found that the drag increases with an increase in the yaw angle, but surprisingly the drag remains constant for yaw angles within the interval ±0.5° for which the side force displays very large fluctuations. This plateau is explained by recent observation of the bi-stable properties of the squareback Ahmed body (Grandemange, et al., 2012). The suppression of the bi-stable behavior using a passive control technique is associated with an additional drag reduction of 1.6%. Abstract : Highlights: The drag is optimized by chamfering the trailing edges. The optimum is interpreted as a compromise between reducing wake thickness and producing 3D separation (induced wake). This result at full scale was firstly observed at smaller scale in Grandemange et al. (2013). The contribution of 3D separation (longitudinal vortices) is clearly evidenced in Fig. 12 by studying 3 configurations of trailing edge chamfers. Sideslip measurements evidence the bi-stable behavior of the wake as recently discovered at Laboratory scale in Grandemange et al. (2013). Bi-stability suppression using the same control technique developed at laboratory scale in Grandemange et al. (2014) is able to reduce the drag, thus confirming the additional drag due to instantaneous asymmetric wake.